2020
DOI: 10.1029/2019jg005316
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Nitrogen Additions Alter Chemical Composition and Turnover of the Labile Fraction Soil Organic Matter via Effects on Vegetation and Microorganisms

Abstract: Global nitrogen (N) deposition greatly impacts soil carbon sequestration. A 2-yr multiple N addition (0, 10, 20, 40, 80, and 160 kg N·ha −1 ·yr −1 ) experiment was conducted in alpine grassland to illustrate the mechanisms underlying the observed soil organic matter (SOM) dynamics on the Qinghai-Tibet Plateau (QTP). Labile fraction SOM (LF-SOM) fingerprints were characterized by pyrolysis-gas chromatography/tandem-mass spectrometry, and microbial functional genes (GeoChip 4.6) were analyzed in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Growth of PA in variant 3, at first sight, contradicts the thesis that mineral forms of N inhibit protease activity (Piotrowska-Długosz, 2020; Tian et al, 2020). Obviously, straw + N 30 P 45 K 45 reduced N-restriction on microbial biomass formation and P-restriction on metabolic processes in microorganisms (Chen et al, 2017), directly or indirectly activating the growth and reproduction of bacteria and fungi by changing their ratio (Li et al, 2019;Chen et al, 2020). This may, at least in part, be the reason for the activation of enzyme synthesis and secretion (Piotrowska-Długosz, 2019), in particular, the growth of PA. Changes in hydrolase activity were accompanied by a predictable increase, probably in the content of C and N nutrients and, consequently, a documented increase in C-LH, DA (Bowles et al, 2014;Singh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth of PA in variant 3, at first sight, contradicts the thesis that mineral forms of N inhibit protease activity (Piotrowska-Długosz, 2020; Tian et al, 2020). Obviously, straw + N 30 P 45 K 45 reduced N-restriction on microbial biomass formation and P-restriction on metabolic processes in microorganisms (Chen et al, 2017), directly or indirectly activating the growth and reproduction of bacteria and fungi by changing their ratio (Li et al, 2019;Chen et al, 2020). This may, at least in part, be the reason for the activation of enzyme synthesis and secretion (Piotrowska-Długosz, 2019), in particular, the growth of PA. Changes in hydrolase activity were accompanied by a predictable increase, probably in the content of C and N nutrients and, consequently, a documented increase in C-LH, DA (Bowles et al, 2014;Singh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the increase in variant 2 Introduction of straw + N 30 P 45 K 45 in variant 3 obviously led to a decrease in the C:N ratio in the soil and, consequently, to an increase in the rate of consumption of high-carbon organic compounds by microorganisms compared to the control. The intake of N levelled the restriction of the activity of C-metabolic enzymes, and caused an increase in their activity (Chen et al, 2020), in particular CA. Growth of PA in variant 3, at first sight, contradicts the thesis that mineral forms of N inhibit protease activity (Piotrowska-Długosz, 2020; Tian et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the above-mentioned POXC, CWEOC, HWEOC, DOC can affect the values of CA, PA, DA, and serve as output pools of OC for the formation of a more "mature" C-LH. It is possible that DOC (80°C), dissolved organic nitrogen DON (25, 80°C), and hot water-extracted organic nitrogen HWEON Zhao et al, 2016) of IN form in fertilisers (Chen et al, 2020) and in the soil, easily hydrogenated nitrogen, MBC, N microbial biomass MBN, etc. Notably, the health, quality, productivity, and fertility of the soil are characterised by complex indices, which include enzymatic activities within one or more processes, the content of soluble forms of OC, soil respiration, pH, etc.…”
Section: Resultsmentioning
confidence: 99%
“…For example, N addition stimulated NEE mainly by increasing the cover of dominant species in alpine meadows ( Shen H. et al, 2022 ). Nitrogen-induced shifts in plant functional groups are considered to be an essential factor affecting carbon exchange in ecosystems ( Niu et al, 2010 ; Fang et al, 2011 ; Chen et al, 2020 ), generally favoring a few nitrophilic plant species while suppressing the growth of many other species ( Duprè et al, 2010 ; Jiang et al, 2012 ). In addition, studies showed that an increase in soil respiration was positively related to soil nutrient availability under N addition ( Leff et al, 2015 ; Peng et al, 2015 ; Riggs et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%